From City of Kings to Metropolitan Lima - Robles Mendoza, Román (2022)
In this paper we approach the issue of the spectacular growth of the city of Lima, with information from the forties and by extension of the entire last century. For this purpose, we resort to sources of information from authors who have studied the capital city, migration from the countryside to the city, and the study of slums. We complement the essay with data from our personal experience, with which we make a tight diachronic summary of the demographic development of the metropolis.